Intraoperative Cycling Pressure Variation in the Treatment of Central Retinal Artery Occlusion - A. Altun (Case Reports in Ophthalmological Medicine)
A 45-year-old male presented to the clinic of ophthalmology with central retinal artery occlusion (CRAO). There was no response to medical treatment, ocular massage, and anterior chamber paracentesis. CRAO was resolved by pars plana vitrectomy and intraoperative cycling pressure variation. The best-corrected visual acuity improved to 20/100 on the first day and to 20/20 on the first month, postoperatively.